Routledge handbook of ecotourism - Fennell, David A., 1963- (Routledge international handbooks, 2022)
"This handbook presents a timely, broad-ranging and provocative overview of the essential nature of ecotourism. The chapters will both advance the existing central themes of ecotourism and provide challenging and divergent observations that will thrust ecotourism into new areas of research, policy and practice. The volume is arranged around four key themes: sustainability, ethics and identity, change, conflict and consumption, and environment and learning, with a total of 28 chapters. The first section focuses on sustainability as a core ecotourism criterion, with a primary focus on some of the macro sustainability issues that have an impact on ecotourism. Foremost among these topics is the linkage to the UNs sustainable development goals, which have relevance to ecotourism as one of the greenest or most responsible forms of tourism. The chapters in the second section provide a range of different topics that pull ecotourism research into new directions, including a chapter on enriching indigenous ecotourism through culturally sensitive universalism. The third section includes chapters on topics ranging from persons with disabilities as a neglected body of research in ecotourism, to ecotourism as a form of luxury consumption. The final section emphasises the link between ecotourism and learning about the natural world, including a deeply theoretical chapter on rewilding Europe. With contributions from authors around the world, this handbook gives a global platform to local voices, in both developed and emerging country contexts. The multidisciplinary and international Routledge Handbook of Ecotourism will be of great interest to researchers, students and practitioners working in tourism and sustainability"--